Prognostic value of tumor-infiltrating T-lymphocytes density in the therapeutic response to initial platinum-based chemotherapy in patients with non-small cell lung cancer: / - Novaković Lacković, Lora; Tadić Latinović, Ljilja; Stanetić, Mirko; Lacković, Marko (Vojnosanitetski pregled, 2023)
Background/Aim. The fact that lung carcinomas, like other solid tumors, can be immunogenic may have a substantial prognostic value in non-small cell lung cancer (NSCLC). Specific cytotoxic T-lymphocytes (CTL) can be demonstrated in most patients with primary tumors of different histological types. Two main groups of T-lymphocytes participate in the coupled recognition of tumor-specific antigens – CTL (CD8+) and helper T-lymphocytes (CD4+). The aim of the study was to assess the relationship between the tumor infiltration of T-lymphocytes and the therapeutic response to initial chemotherapy. Methods. Data were obtained from patients with NSCLC whose therapeutic response after four cycles of initial platinum-based chemotherapy was observed in relation to the density of tumor-infiltrating T-lymphocytes (CD4+ and CD8+) in small tumor biopsy samples. The therapeutic response was assessed in line with Response Evaluation Criteria in Solid Tumors (RECIST) 1.1 therapeutic response evaluation system. Based on the expected therapeutic response, the patients were divided into three groups: favorable therapeutic response patients (complete and partial regression), stable disease patients, and disease progression patients. To assess the density of CD4+ and CD8+ T-lymphocytes, the number of lymphocytes was determined at ×200 magnification (1.1 mm2). Three visual fields with the densest lymphocyte infiltrate were selected for counting, and the values of all individual fields were added up. Based on the mean value, the samples were classified into the following groups: score 0, score 1, score 2, and score 3. During statistical data processing, low infiltration density combined score 0 and score 1 groups, and high infiltration density combined score 2 and score 3 groups. Based on the collected data, a database was created in SPSS 22.0 software and used for further statistical analysis. Statistical analysis of the data included descriptive and analytical statistics methods. Results. There was no significant difference in the distribution of CD4+ T-lymphocytes and CD8+ T-lymphocytes in the epithelial component of the tumor between patients with a different therapeutic response (χ2 = 2.977; p = 0.226 and χ2 = 1.329; p = 0.515, respectively). There was no significant influence of the infiltration density of CD4+ T-lymphocytes and CD8+ T-lymphocytes in the stromal component of the tumor on the therapeutic response (χ2 = 0.606; p = 0.739 and χ2 = 5.167; p = 0.076, respectively). Conclusion. The research did not prove that patients with a high level of tumor-infiltrating CD4+ and CD8+ T-lymphocytes in the epithelial and stromal component of the NSCLC had a better therapeutic response to standard initial chemotherapy.
Keywords: carcinoma, non-small cell lung; cd4-positive t-lymphocytes; prognosis, t-lymphocytes; t-lymphocytes, cytotoxic; treatment outcome